2012
DOI: 10.1021/ja303480a
|View full text |Cite
|
Sign up to set email alerts
|

Bis(allyl)zinc Revisited: Sigma versus Pi Bonding of Allyl Coordination

Abstract: The reinvestigation of two allyl zinc compounds, parent bis(allyl)zinc [Zn(C(3)H(5))(2)] (1) and 2-methallyl chloro zinc [Zn(C(4)H(7))Cl] (2), revealed two new coordination modes in the solid state for the allyl ligand, viz cis- and trans-μ(2)-η(1):η(1). These results call for modification of the conventional interpretation of zinc-allyl interactions. Computational results indicate that the classical η(3)-bonding mode of the allyl ligand is not favored in zinc compounds. A rare case of a zinc-olefin interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0
10

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(56 citation statements)
references
References 98 publications
5
41
0
10
Order By: Relevance
“…In agreement with the Zn-allyl interaction mode previously reported in the literature (in solution, but also in solid state and in the gas phase), [23] EtZn is sbonded to the allyl motif in 3 1 .This type of coordination frees the rotation between C 2 and C 3 (Scheme 4), thus leading to potentially fast equilibration between 3 1 and 3 1 ' ',inagreement with the low rotation barrier of 5kcal mol À1 defined by 3-TS 1 rot (see the Supporting Information). In agreement with the Zn-allyl interaction mode previously reported in the literature (in solution, but also in solid state and in the gas phase), [23] EtZn is sbonded to the allyl motif in 3 1 .This type of coordination frees the rotation between C 2 and C 3 (Scheme 4), thus leading to potentially fast equilibration between 3 1 and 3 1 ' ',inagreement with the low rotation barrier of 5kcal mol À1 defined by 3-TS 1 rot (see the Supporting Information).…”
Section: Methodssupporting
confidence: 91%
See 1 more Smart Citation
“…In agreement with the Zn-allyl interaction mode previously reported in the literature (in solution, but also in solid state and in the gas phase), [23] EtZn is sbonded to the allyl motif in 3 1 .This type of coordination frees the rotation between C 2 and C 3 (Scheme 4), thus leading to potentially fast equilibration between 3 1 and 3 1 ' ',inagreement with the low rotation barrier of 5kcal mol À1 defined by 3-TS 1 rot (see the Supporting Information). In agreement with the Zn-allyl interaction mode previously reported in the literature (in solution, but also in solid state and in the gas phase), [23] EtZn is sbonded to the allyl motif in 3 1 .This type of coordination frees the rotation between C 2 and C 3 (Scheme 4), thus leading to potentially fast equilibration between 3 1 and 3 1 ' ',inagreement with the low rotation barrier of 5kcal mol À1 defined by 3-TS 1 rot (see the Supporting Information).…”
Section: Methodssupporting
confidence: 91%
“…Thes econd stereochemical issue arises from the reaction of 3 1 with PhCOCl. In agreement with the Zn-allyl interaction mode previously reported in the literature (in solution, but also in solid state and in the gas phase), [23] EtZn is sbonded to the allyl motif in 3 1 .This type of coordination frees the rotation between C 2 and C 3 (Scheme 4), thus leading to potentially fast equilibration between 3 1 and 3 1 ' ',inagreement with the low rotation barrier of 5kcal mol À1 defined by 3-TS 1 rot (see the Supporting Information). Among all the possible transition states examined for the reaction of the allylzinc species with PhCOCl, the lowest in energy follows the Zimmerman-Traxler model.…”
Section: Methodssupporting
confidence: 91%
“…The effect that this might have on the relative stability of η 3 ‐ over η 1 ‐ bonding was examined with a DFT computational investigation (B3PW91‐D3BJ/def2TZVP) of a selected set of [M II A′ 2 ] and [KM II A′] 3 (M II =Be, Mg, Zn, Sn) complexes (for details see the Supporting Information). In the optimized [MA′ 2 ] complexes, Zn and Sn have η 1 ‐bound allyls, indicating a preference that is corroborated by the lack of any structurally authenticated η 3 ‐bound allyls on Zn, though some have recently been identified for Sn . For the more electropositive elements (Be, Mg), [M(η 3 ‐A′) 2 ] geometries are lower in energy than the [M(η 1 ‐A′) 2 ] counterparts; the preference for η 3 ‐ over η 1 ‐ in the case of Be is small (4.4 kcal mol −1 ), but it doubles to 9.0 kcal mol −1 for Mg…”
Section: Resultsmentioning
confidence: 93%
“…[31] Thee lectronegativity of Mg (1.31, Pauling scale [32] )isless than any of other divalent metals used to date (1.57, 1.65, and 1.80 for Be,Zn, and Sn, respectively), however, and the Mg À Cb ond is somewhat more polar than the other M À Cc ases.T he effect that this might have on the relative stability of h 3 -o ver h 1 -b onding was examined with aD FT computational investigation (B3PW91-D3BJ/ def2TZVP) of as elected set of [M II A' 2 ]a nd [KM II A'] 3 (M II = Be,M g, Zn, Sn) complexes (for details see the Supporting Information). In the optimized [MA' 2 ]complexes, Zn and Sn have h 1 -bound allyls,indicating apreference that is corroborated by the lack of any structurally authenticated h 3bound allyls on Zn, [33] though some have recently been identified for Sn. [34] Fort he more electropositive elements (Be,Mg), [M(h 3 -A') 2 ]geometries are lower in energy than the [M(h 1 -A') 2 ]counterparts;the preference for h 3 -over h 1 -inthe case of Be is small (4.4 kcal mol À1 ), but it doubles to 9.0 kcal mol À1 for Mg. [35] Calculations on the monomeric [KM II A' 3 ]c omplexes indicated that all of them were at least local minima on their respective potential energy surfaces.The reason that amonomeric [KMg(h 1 -A') 3 ]c omplex is not isolated may be largely ar esult of the preference of magnesium for h 3 -o ver h 1 -allyl bonding.F urthermore,t he polymeric structure of 1 provides for an h 3 -i nteraction of the allyls with K + ,w hich should provide greater stabilization than that from the h 2 cation-p interactions with the C=Cd ouble bonds in a[ KMg(h 1 -A') 3 ] complex.…”
Section: Isolated Complexes Involving the A' Ligand And Am Onovalent/mentioning
confidence: 90%